1996
DOI: 10.1159/000154317
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Environmental Effects on Urinary Kallikrein, Catecholamines, Sodium, Potassium, Urea Nitrogen and Inorganic Sulfate Sulfur Levels in School-Age Twins

Abstract: A genetic analysis of twins at school was undertaken using as variables urinary concentrations of kallikrein, catecholamines, sodium and potassium which have been demonstrated to be associated with blood pressure levels. In addition to these variables, urinary concentrations of urea nitrogen and inorganic sulfate sulfur which are indices of protein intake were investigated. 35 pairs of monozygotic twins and 19 pairs of dizygotic twins aged from 6 to 14 years were examined. Variance and correlation tests for ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…A second study of 30 matched stone formers and controls did not find a difference in total excretion [18]. In addition, a twin study suggested that urinary sulfate levels are determined largely by environment, rather than genetics [19].…”
Section: Discussionmentioning
confidence: 92%
“…A second study of 30 matched stone formers and controls did not find a difference in total excretion [18]. In addition, a twin study suggested that urinary sulfate levels are determined largely by environment, rather than genetics [19].…”
Section: Discussionmentioning
confidence: 92%
“…They also reported that diminished response of renal TK excretion to orally administered KCl is demonstrated in African-Americans compared with white [18]. In another study, hereditary factors affect on urinary K + , Na + and TK excretion in Japanese by a genetic analysis of 35 pairs of monozygotic twins and 19 pairs of dizygotic twins in school children [19].…”
Section: Introductionmentioning
confidence: 96%